2019
DOI: 10.17509/jsl.v3i1.17557
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Student Creative Thinking Skill using CBL Implemented in STEM Education and Combined with PSL Worksheet in Indonesian School

Abstract: The main goal of this study is to present the effectiveness improvement of student’s creative thinking skills using CBL implemented in STEM education and CBL combined with worksheet PSL. The STEM education perspective used in this study is a separate science discipline (Physics) that incorporates other disciplines. The research method used in this study is a quantitative method with a quasi-experimental research design. The research includes a pre-test-post test control group design. The subjects of the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…The existence of integration between disciplines in STEM learning indirectly trains problem solving skills in real life and is able to train 21 st century skills to face future careers [2]. Several studies such as that conducted by [3][4][5] showed that STEM learning was able to improve creative thinking skill. STEM learning integrates several disciplines, namely science, technology, engineering, and mathematics, presents content that is related to real life so that it triggers students to combine content across content in solving problems.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of integration between disciplines in STEM learning indirectly trains problem solving skills in real life and is able to train 21 st century skills to face future careers [2]. Several studies such as that conducted by [3][4][5] showed that STEM learning was able to improve creative thinking skill. STEM learning integrates several disciplines, namely science, technology, engineering, and mathematics, presents content that is related to real life so that it triggers students to combine content across content in solving problems.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the research conducted by (Arnelia & Hardiyanti, 2023), are shown in Figure 2. (Dilekci & Halit, 2023;Putra, 2022;Putri et al, 2019). One way to develop students' thinking abilities is by providing open-ended questions related to problems in everyday life (Damayanti & Sumardi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Training is needed to develop this thinking ability. Creative thinking abilities can be developed through skills training(Dilekci & Halit, 2023;Putra, 2022;Putri et al, 2019). One way to develop students' thinking abilities is by providing open-ended questions related to problems in everyday life(Damayanti & Sumardi, 2018).…”
mentioning
confidence: 99%
“…Student worksheet is a component of teaching materials that includes activities aimed at assisting students in finding information that is relevant to the learning objectives (Monika & Ramadan, 2022;Prasadi et al, 2020). Student worksheet is a method for students to actively find their own knowledge during the learning process (Haidir et al, 2021;Putri et al, 2019). Student worksheet can also greatly increase the quality of student learning.…”
Section: Introductionmentioning
confidence: 99%